ANALISIS LOW FLOW MENGGUNAKAN MODEL HEC-HMS UNTUK KASUS SUB DAS KRANGGAN - Marhendi, Teguh (Techno Jurnal Ilmu Teknik, 2010)
Rainfall-runoff transformation, is a very complex process. Rain input contains space and time which is very high variability and can not be predicted for the future. Thus would require a very complex hydrological analysis and huge calculating. The analysis can be done by assuming a transformation process occurs following certain conditions. This conditions or rules is known as the hydrologic model.This paper attempts to analyze the low flow in Subdas Kranggan at Borobudur using HEC-HMS 3.1 Software. HMS3.1 HEC (Hydrologic Modeling System) is designed to calculate the rainfall-flow processes of a DAS system. This software was developed by the Hydrologic Engineering Center (HEC) of the U.S. Army Corps of Engineering (2005), which was developed from HEC-1. HEC-HMS 3.1 have calibration facilities, the ability to simulate the distribution model, continuous model and the ability to read GIS data.Based on sensitivity analysis, surface capacity parameters and max infiltration rate is large enough to influence the calibration results changing when both parameters changed its magnitude. Changing calibration result due to the parameters sensitivity of surface capacity, and max infiltration rate indicates that this parameter is very sensitive to changes that occur in these sub DAS or magnitude of these parameters greatly affect to the annual water flow system in that sub DAS.Â Keywords: Low flow, HEC-HMS 3.1, Subdas Kranggan